BUDAYA DAN KARAKTER BANGSA - Abdul Manaf (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2019)
Character is a behavior which is showed by a person in his environment either utterances, writing, performance or the way to express himself to face social character in daily life. So, character can be referred to the way of thinking and acting which is a typical in life and cooperating in family, society and nation. The qualified individual is one who can make decision and be responsible to consequence he already did. Furthermore, the character also means individuality, behavior, moral, or personality which is formed from internalization of various virtues and is believed and used as base to view, thought, act and behavior.